Pre‐ to post‐inpatient treatment of subjective sleep quality in 5, 481 patients with mental disorders: A longitudinal analysis. (24th March 2019) - Schennach, Rebecca; Feige, Bernd; Riemann, Dieter; Heuser, Jörg; Voderholzer, Ulrich
Abstract: There is only limited evidence of the course of sleep quality and sleep disturbances during acute inpatient treatment and the prediction of/association with treatment outcome in mental disorders. Within this naturalistic study, 5, 481 consecutively admitted inpatients completed the Pittsburgh Sleep Quality Index (PSQI) and the Beck Depression Inventory (BDI‐II) at admission and at discharge. Treatment included both individual and group psychotherapy (but no specific interventions for sleep disturbances) and pharmacotherapy based on current national treatment guidelines. Correlation analyses, analyses of variance and linear models were calculated to analyse the datasets. The PSQI improved significantly ( p  < 0.001) from admission (mean score 9.51 [±4.11]) to discharge (mean score 8.08 [±4.20]) in all diagnostic subgroups. Despite this improvement, 47% of the patients still showed elevated PSQI scores (>5) at discharge. Patients with post‐traumatic stress disorder showed the largest sleep disturbances at both time‐points; patients with obsessive‐compulsive disorder were the least impaired. An improvement of the PSQI was found to be significantly correlated ( p  < 0.001) to the change of BDI‐II values (without the sleep item) during treatment. The likelihood of achieving remission of depressive symptoms (BDI‐II total score <14) was significantly associated with less sleep disturbances at admission. The results suggest that almost half of inpatients with mental disorders treated successfully with state‐of‐the art specific psychotherapy and pharmacotherapy do not have remission of their sleep problems. Therefore, specific treatment programmes for insomnia should be evaluated and implemented in daily clinical routines.